Influence of polysulfone and hemophan hemodialysis membranes on phagocytes - Kubala, L; Cíz, M; Soska, V; Cerný, J; Lojek, A (General physiology and biophysics, 2002)
The aim of the study was to compare the effect of hemophane and polysulfone membranes on the phagocyte-derived production of reactive oxygen species (ROS) as well as on neutrophil CD11b and CD62L expression in patients undergoing regular hemodialysis. The effects of hemodialysis membranes were also studied in in vitro conditions after coincubating them with differentiated HL-60 cells. ROS production was measured using chemiluminometric and flow cytometric methods. Expression of CD11b, CD62L and mitochondrial membrane potential were detected by monoclonal antibodies and by the JC-1 fluorescent probe, respectively. Depressed ROS production was observed in patients already before dialysis. Further decrease in ROS production and an increase in CD11b expression were observed especially in patients after hemophan hemodialysis. Decreased ROS production and increased CD11b expression were observed also after incubation of HL-60 cells with hemophan membranes. Mitochondrial membrane potential dropped only after incubating cells with hemophan membranes proving its more serious adverse effects in comparison with the polysulfone membrane. In conclusion, deleterious effects of hemodialysis on the metabolic activity of phagocytes were proved. Combining chemiluminescent and flow cytometric methods for the detection of ROS production and determining mitochondrial membrane potential can be useful tools for the analysis of material biocompatibility.
Keywords: HL-60 buňky; Female; Renal Dialysis; biokompatibilní materiály; dialýza ledvin; L-selektin; Phagocytes; ženské pohlaví; CD11b Antigen; Polymers; sulfony; lidé; membrány umělé; Sulfones; Reactive Oxygen Species; Aged, 80 and over; HL-60 Cells; fagocyty; Membranes, Artificial; Middle Aged; Biocompatible Materials; celulosa; Male; Aged; L-Selectin; polymery; reaktivní formy kyslíku; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Cellulose; antigeny CD11b; Humans